2016
DOI: 10.1165/rcmb.2016-0060tr
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Apolipoprotein E and Apolipoprotein A-I in the Pathogenesis and Treatment of Lung Disease

Abstract: Emerging roles are being recognized increasingly for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 98 publications
(110 reference statements)
3
92
0
Order By: Relevance
“…have been already-ample evidence showing that the pathogenic ApoE leads to an abnormal response of microglia to amyloid deposition in the brain (34,36,38). Currently, there is no evidence indicating a causal link between ApoE polymorphism and lung fibrosis (39). However, given that organ fibrosis, including IPF, normally occurs in the aged population, much like most of the neurodegenerative diseases, we are certainly intrigued to undertake such an investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…have been already-ample evidence showing that the pathogenic ApoE leads to an abnormal response of microglia to amyloid deposition in the brain (34,36,38). Currently, there is no evidence indicating a causal link between ApoE polymorphism and lung fibrosis (39). However, given that organ fibrosis, including IPF, normally occurs in the aged population, much like most of the neurodegenerative diseases, we are certainly intrigued to undertake such an investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE interacts with the low-density lipoprotein receptor (LDLR) to mediate the transport of cholesterol-and triglyceride-rich lipoprotein particles into cells via receptor-mediated endocytosis [27]. In contrast, apoAI is the major protein constituent of high-density lipoprotein (HDL) that mediates reverse cholesterol transport out of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, apoAI is the major protein constituent of high-density lipoprotein (HDL) that mediates reverse cholesterol transport out of cells. ApoE and apoA1 are synthesized primarily in the liver but can also be expressed by lung cells where they help attenuate inflammation, oxidative stress, and tissue remodeling responses, while augmenting adaptive immunity and host defense [27]. ApoE receptor 2, one of the LDLR family members expressed in macrophages, can bind to its ligand apoE, exhibiting an anti-inflammatory role in atherosclerosis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apo-A1 has been proved to be associated with many cancer, furthermore, it could be used as a potential biomarker for detection and diagnosis for many cancers such as bladder cancer [15,16]. In a recent study, researchers observed that lower serum levels of Apo-A1 in thyroid cancer patients compared to healthy controls, indicating that Apo-A1 may play an anti-tumor role in thyroid cancer [17].…”
Section: Discussionmentioning
confidence: 99%